Grido; Reigen seliger Geister; Gran Torso - Lachenmann, Helmut 1935-; Arditti Quartet (Vienna Kairos, 2007)
The three quartets provide a commentary on each other and the time in which they were composed. Gran Torso has something of an investigation about it, of a broaching, of forays into critical new land. Reigen designates the sounds and techniques of two very different regions. Grido gains a new expressiveness the land of music is freely praised and celebrated, although never without reflexive refraction or arousing disturbance. In the Choral at the end comes a sharp crack, a bark, before the music collapses.(Martin Kaltenecker)
Grido String Quartet Nr.3 (2001/02) -- Reigen seliger Geister String Quartet Nr.2 (1988/89) -- Gran Torso Music for String Quartet (1971-72/78)
Keywords: 20th Century (1901-2000); String quartet; Avant-garde; Germany